1992
DOI: 10.4049/jimmunol.149.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetics of collagen-induced arthritis in rats. Both MHC and non-MHC gene products determine the epitope specificity of immune response to bovine and chick type II collagens.

Abstract: Seven inbred, RT1-congenic rat strains were immunized with native bovine (BII), porcine (PII), or chick (CII) type II collagen and observed for onset, incidence, and severity of arthritis. Clinical results were compared with IgG reactive with native rat type II collagen (RII) and the purified, renatured cyanogen-bromide peptides of BII, CII, or RII. Immunodominant responses to CB11, CB9,7, and CB12 of RII were identified. Secondary responses to CB8 and CB10 also occurred. Reproducible patterns of peptide react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Despite the variety of rat strains bearing different MHC types that are susceptible to collagen II-induced arthritis, the incidence rate, magnitude of symptoms, and CIA severity could be different. This also includes antibodies and the scope of the T-cell reactive epitope specificity [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the variety of rat strains bearing different MHC types that are susceptible to collagen II-induced arthritis, the incidence rate, magnitude of symptoms, and CIA severity could be different. This also includes antibodies and the scope of the T-cell reactive epitope specificity [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This point makes a bridge between the features of the autoimmune disease model and the antigenic specificity of the MHC proteins in the animals used for modeling the disease [28,29]. It is known that rat strains with different MHC types are able to develop CIA, although the autoantibody specificities or T-cell epitope affinities may differ among the rat strains significantly [30]. For instance, DA and SD rats have distinct MHC RT1 haplotypes av1 and f respectively [25,29].…”
Section: Introductionmentioning
confidence: 99%
“…Arthritic responses to chick and bovine CII are often equivalent, with the notable exception of ACI and BN rats where disparate responses are seen. Studies by Griffiths et al (1992) have also shown that the arthritis-producing potential of porcine CII is essentially identical to that of bovine and human CII.…”
Section: 522mentioning
confidence: 92%
“…Arthritis has been induced in highresponder strains of rats with CII purified from the cartilage of a number of species-e.g., human, chick, bovine, porcine, rabbit, guinea pig, and deer. With the unique exception of the DA rat (Griffiths et al, 1993), most strains respond poorly to rat CII compared to other mammalian and avian products (Griffiths et al, 1992;Cremer et al, 1994). Arthritic responses to chick and bovine CII are often equivalent, with the notable exception of ACI and BN rats where disparate responses are seen.…”
Section: 522mentioning
confidence: 99%